2020
DOI: 10.1017/s1751731119003422
|View full text |Cite
|
Sign up to set email alerts
|

Are there consistent relationships between major connective tissue components, intramuscular fat content and muscle fibre types in cattle muscle?

Abstract: Intramuscular connective tissue (IMCT) is mainly composed of several fibrils (known as total collagen (TCol)) linked between each other by different chemical cross-links (CLs), the whole being embedded in a matrix of proteoglycans (PGs). In the field of beef quality, there is limited information on the role of CLs and PGs. Accordingly, several authors suggest that, to investigate the role of IMCT, it is important to investigate them just like TCol and insoluble collagen (ICol). In muscle, there are two other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
3
18
0
1
Order By: Relevance
“…The low abundance of PKM, GPI and PGK1 in the oxidative highly marbled LT muscle was also consistent with the negative correlation between the abundance of these proteins and the IMF values reported by Bazile et al [22]. Among proteins annotated by the GO term (GO:0006099) involved in tricarboxylic acid cycle, FH, DLST and MDH2 were less abundant in the ST muscle, LT and SM being equal in accordance with the contractile and metabolic properties of these muscles described in the literature [39].…”
Section: Muscle Type Effect Of Candidate Biomarkers Of Beef Tenderness or Marblingsupporting
confidence: 90%
“…The low abundance of PKM, GPI and PGK1 in the oxidative highly marbled LT muscle was also consistent with the negative correlation between the abundance of these proteins and the IMF values reported by Bazile et al [22]. Among proteins annotated by the GO term (GO:0006099) involved in tricarboxylic acid cycle, FH, DLST and MDH2 were less abundant in the ST muscle, LT and SM being equal in accordance with the contractile and metabolic properties of these muscles described in the literature [39].…”
Section: Muscle Type Effect Of Candidate Biomarkers Of Beef Tenderness or Marblingsupporting
confidence: 90%
“…The differences in biochemical composition between the M and AT are presented elsewhere. 16 For any comparisons including interactions, a Student-Newman-Keuls test was used to separate the least-squares means (LSmeans). P < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The muscles were removed from carcasses 48 h post mortem using the same protocol, between the fifth and tenth rib for LT and from the middle part of the muscle for ST, SM and RA. 16 Each muscle was divided into two parts. The first one was stored under vacuum for 7 days for ageing, and then stored at −20°C until sensory analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle fiber types significantly affect glycogen and mitochondria contents, determined the glycolytic rate, then influenced myofibrillar protein degradation, enzymatic activity of glycolytic enzymes and calcium‐dependent proteolysis system, and finally affected the ultimate meat quality (Choi & Kim, 2009; Picard & Gagaoua, 2020). Studies showed that total collagen, insoluble collagen, and chemical cross‐links were positively and negatively correlated with type IIA and IIB + X muscle fibers, insoluble collagen, and sensory tenderness was correlated with type I muscle fibers in cattle muscle, regardless of muscle and animal type (Listrat, Gagaoua, Normand, Andueza, et al, 2020; Listrat, Gagaoua, Normand, Gruffat, et al, 2020). Type IIB muscle fibers have higher calpain/calpastatin ratios compared to type I fibers in porcine muscle; myosin heavy chain (MHC) slow isoform contents are positively correlated with calpastatin activity (Choi & Kim, 2009; Ouali & Talmant, 1990).…”
Section: Introductionmentioning
confidence: 99%